Factors that influence the performance of conventional and Islamic banks / Nur Izzatur Fatihah Muhammad Tahir - Muhammad Tahir, Nur Izzatur Fatihah (2022)
This research intends to closely examine factors that influence conventional and Islamic banks based on their profitability in Malaysia. Money is treated as a commodity in conventional banks, who lend it against interest as recompense. On the other hand, the products of Islamic banking usually are asset-backed and comprise asset rental, asset trading, also profit-and-loss participation. Despite this, it is also thought that customers and banks have a relationship of creditor and debtor. Having said that, the secondary data was drawn from five conventional banks which is Maybank, Public Bank, Affin Bank, CIMB Bank and Hong Leong Bank while for Islamic banks are Bank Islam, Bank Muamalat, MBSB Bank, Hong Leong Islamic Bank and CIMB Islamic Bank retrace from the year 2010 to 2021 consisting of 120 set of data. This study seeks to examine whether the cost of funds, cost of labour, cost of capital and interbank lending influences the profitability of the Islamic and conventional bank. Then again, how this may vary between Islamic and conventional banks in Malaysia. Our findings indicate that cost of funds from Islamic banks has significant relationship with the dependent variable, profitability in overall results.